Pengaruh Pancasila Buddha Dalam Meningkatkan Kualitas Diri - Untung, Syamsul Hadi; Rizal, Abdullah Muslich; Harefa, Rizka Rahmi; Putri, Levina; Fitriana, Hafifah; Hayatina, Hana (Jounal Nyanadassana, 2023)
This study aims to analyze the application of Buddhist Pancasila to determine the effect of Pancasila in improving self quality, this research was conducted in the form of mixed methods (mix methods) literature and field studies at STAB Nalanda. This research concludes that the Buddhist Pancasila are five moral rules that train one's self to be able to behave well when entering Buddhist life. Buddhist Pancasila has an important influence in shaping the quality of self and mentality in order to fulfill the requirements as a human being as recorded in the Tripitaka book which is a history in the formation of Pancasila through Sidharta's story whendoing meditation, this includes elements that are also related to Indonesian Pancasila as the foundation of state rules.